2014
DOI: 10.1002/sia.5557
|View full text |Cite
|
Sign up to set email alerts
|

Studies of degradation behaviors of poly (3‐hexylthiophene) layers by X‐ray photoelectron spectroscopy

Abstract: Degradation behaviors of poly(3‐hexylthiophene‐2,5‐diyl) (P3HT) layers on NiO in the presence of H2O at ambient pressure and dark conditions were studied using X‐ray photoelectron spectroscopy (XPS). Upon H2O exposure at 120 °C, partial oxidation of P3HT together with molecular water incorporation, but with the maintained local ring‐structure, were deduced by XPS. Valence band spectra of XPS evidenced that the partial oxidation of P3HT local structure could alter π‐conjugation systems of P3HT layers, forming a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Additionally, the de-convoluted high-resolution O 1 s core level spectra depicted in Fig. 8b resulted in two bands: the lower BE = 530 eV is assigned to oxygen bonded with zinc and the higher BE band located at about 532 eV resulting from oxygen impurities incorporated in P3HT [ 67 69 ]. It is however important to note that the Ar + ion sputtering causes the reduction of oxygen impurities concentration in P3HT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the de-convoluted high-resolution O 1 s core level spectra depicted in Fig. 8b resulted in two bands: the lower BE = 530 eV is assigned to oxygen bonded with zinc and the higher BE band located at about 532 eV resulting from oxygen impurities incorporated in P3HT [ 67 69 ]. It is however important to note that the Ar + ion sputtering causes the reduction of oxygen impurities concentration in P3HT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was not possible to distinguish these apart with the PTB7 material system. Nevertheless, previous reports of donor acceptor copolymers indicate that the main chain decomposes upon ageing [12,14]. This will almost certainly have an impact upon the photophysical properties and conductivity of the polymer.…”
Section: Exposing Ptb7 To Different Environmentsmentioning
confidence: 96%
“…Most XPS work has focused on studying the degradation of P3HT using XPS, for example, Hintz et al looked at exposing P3HT for short periods to oxygen under dark and illumination and showed that both physisorbed and photo-oxidised oxygen is present [13]. Seo et al studied longer term degradation detail and showed the formation of sulfoxide (R-SO-R) on the sulphur atom of the thiophene ring [14]. Changes in the oxidised C 1s spectra were mostly attributed to degradation of the side chain, in particular C-OH (alpha-unsaturated alcohol).…”
Section: Introductionmentioning
confidence: 99%
“…25 XPS spectra (S 2p and C 1s core-level) of the as-prepared P3HT/ZnO ripple sample were repeatedly obtained after back-and-forth transfer between the preparation and main chambers. 25 XPS spectra (S 2p and C 1s core-level) of the as-prepared P3HT/ZnO ripple sample were repeatedly obtained after back-and-forth transfer between the preparation and main chambers.…”
Section: In Situ X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…With increasing exposure time to the humid atmosphere with light illumination, growth of a new S 2p state with a 2p 3/2 binding energy of 165.2 eV was observed, which can be assigned to the formation of sulfoxide species (SQO). 25,27,30,31 The three states centered at 285.3, 285.9, and 286.1 eV can be attributed to CQC-C, C-C, and CQC-S groups, respectively, with a relative intensity of 1 : 3: 1, corresponding to the molecular structure of P3HT. 1b shows the results of similar experiments using TiO 2layered ZnO ripples as the substrate of the P3HT layers.…”
Section: In Situ X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%